The Mechanism of Regulated Release of Lasso/Teneurin-2 - Vysokov, Nickolai V.; Silva, John-Paul; Lelianova, Vera G.; Ho, Claudia; Djamgoz, Mustafa B.; Tonevitsky, Alexander G.; Ushkaryov, Yuri A. (Frontiers in Molecular Neuroscience, 2016)
Teneurins are large cell-surface receptors involved in axon guidance. Teneurin-2 (also known as Lasso) interacts across the synaptic cleft with presynaptic latrophilin-1, an adhesion G-protein-coupled receptor that participates in regulating neurotransmitter release. Lasso-latrophilin-1 interaction mediates synapse formation and calcium signaling, highlighting the important role of this trans-synaptic receptor pair. However, Lasso is thought to be proteolytically cleaved within its ectodomain and released into the medium, making it unclear whether it acts as a proper cell-surface receptor or a soluble protein. We demonstrate here that during its intracellular processing Lasso is constitutively cleaved at a furin site within its ectodomain. The cleaved fragment, which encompasses almost the entire ectodomain of Lasso, is potentially soluble; however, it remains anchored on the cell surface via its non-covalent interaction with the transmembrane fragment of Lasso. Lasso is also constitutively cleaved within the intracellular domain. Finally, Lasso can be further proteolytically cleaved within the transmembrane domain. The third cleavage is regulated and releases the entire ectodomain of Lasso into the medium. The released ectodomain of Lasso retains its functional properties and binds latrophilin-1 expressed on other cells; this binding stimulates intracellular Ca2+ signaling in the target cells. Thus, Lasso not only serves as a bona fide cell-surface receptor, but also as a partially released target-derived signaling factor.